2021
DOI: 10.1038/s41598-020-80216-1
|View full text |Cite
|
Sign up to set email alerts
|

Divergent immune landscapes of primary and syngeneic Kras-driven mouse tumor models

Abstract: Immune cells play critical functions in cancer, and mice with intact immune systems are vital to understanding tumor immunology. Both genetically engineered mouse models (GEMMs) and syngeneic cell transplant approaches use immunocompetent mice to define immune-dependent events in tumor development and progression. Due to their rapid and reproducible nature, there is expanded interest in developing new syngeneic tools from established primary tumor models. However, few studies have examined the extent that syng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Consistent with other studies in this field [ 56 , 57 ], the TIME of transplanted KP tumours was more inflamed than spontaneous UPS, showing a 2-fold and 3-fold increase in CD4+ and CD8+ lymphocytes. These finding were also observed on a transcriptomic level as the NanoString® immunological profiling also demonstrated a trend towards higher T cell, adaptive immunity and NK pathways scores in the transplanted model, however these differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with other studies in this field [ 56 , 57 ], the TIME of transplanted KP tumours was more inflamed than spontaneous UPS, showing a 2-fold and 3-fold increase in CD4+ and CD8+ lymphocytes. These finding were also observed on a transcriptomic level as the NanoString® immunological profiling also demonstrated a trend towards higher T cell, adaptive immunity and NK pathways scores in the transplanted model, however these differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 91%
“…These finding were also observed on a transcriptomic level as the NanoString® immunological profiling also demonstrated a trend towards higher T cell, adaptive immunity and NK pathways scores in the transplanted model, however these differences were not statistically significant. In a recent study by Gutierrez et al [ 57 ], examining spontaneous and transplanted Trp53/Kras models of UPS and ERMS, a 2–3 fold increase in CD4 and CD8 lymphocytes were also observed in both models. Similar results have been reported by Riddell et al, showing that spontaneous cre-induced Trp53;Kras KP lung cancer tumours are less immunogenic than transplanted KP lung models [ 58 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, syngeneic cell lines like 4T1 poorly reflect the immunogenicity of human tumors of the same origin (Zhong et al, 2020). Recent research has shown that syngeneic cell lines derived from genetically Cell Reports 38, 110447, March 1, 2022 13 Article ll engineered mouse models (GEMMs) show key differences in their immune landscape, with increased frequencies of T regs , CD8 + T cells, and NK cells, compared with primary tumors in GEMMs (Gutierrez et al, 2021). These differences in immune landscape may critically affect the outcome of immunological studies, and thereby reduce their clinical value compared with GEMM-based models such as the KEP model.…”
Section: Human Brca Treg/nk Ratiomentioning
confidence: 99%
“…However, another study performed similar experiments in the KP model, with conditional Kras G12D mutation plus Tp53 deletion, comparing the immune infiltrates and response to checkpoint blockade in primary tumors to those transplanted into naïve C57Bl/6 mice. Interestingly, in the setting of a low mutational burden tumor, there was no improvement in immunogenicity despite the transplantation, and despite an increase in immune cell infiltration, there was no improvement in response to checkpoint blockade [18] . Finally, a third paper summarized divergent immune landscapes with transplantation of primary KP UPS and rhabdomyosarcoma models into syngeneic recipient mice.…”
Section: Preclinical Investigations In Murine Modelsmentioning
confidence: 99%